Translation Analysis Of Directive Utterances In Novel Of TheAlchemist Into Sang Alkemis (Pragmatic Approach - Utomo, Danang Setyo, Dr.Dwi Haryanti, M.Hum, Siti Fatimah, S. Pd, M. Hum (2014)
This research is to identify the form of translation on the directive utterances, to describe the accurateness of the translation on the directive utterances, and to describe the pragmatic equivalence of directive utterances in novel of the Alchemist into Sang Alkemis. The research is a descriptive research. The writer collets the data by reading the novel, signing the directive utterances, coding the data that included into the directive utterances, and comparing the result of the translation and the original. The data are taken from the Paulo Coelho's novel entitled "The Alchemist" and its translation in Indonesian by Alan R. Clarke entitled "Sang Alkemis". The methods of collecting data is coding. The techniques of analyzing data are clarifying the form of translation directive utterance and its translation referring to grammatical form, describing the accuracy of translation, analyzing the pragmatic equivalence that contains into the directive utterance of the both novel. The results of the research show that: 1) the form of the translation is five categories: imperative sentence is translated into imperative sentence (21.15%), interrogative sentence is translated into interrogative sentence (7.69 %), declarative sentence is translated into declarative sentence (63.46% ), declarative sentence is translated into interrogative sentence (3.85%), and interrogative sentence is translated into declarative sentence (3.85%). 2) The accurateness of translation directive utterance in the novel of Paolo Coelho divided into two parts that categorized in accurateness (80.77%) and inaccurateness (19.23%). 3) The equivalent of the pragmatics of directive utterance is four politeness that include bald on record (26.92 %), off record (34.61 %), positive politeness (26.92 %), and negative politeness (11.54 %).